Claves para rescatar a El Dorador, una crónica perdida de José Martí - Leyva-González, David (2019)
El Dorador is the title of a lost chronicle of José Martí. The Cuban poet, before going to war, asks his secretary and friend Gonzalo de Quesada to rescue this text from his abundant stationery. However, neither Quesada nor the multiple editors Marti has had for more than a century have been able to fulfill this request. The present study offers some clues that bring us closer to this mysterious chronicle. Progressively, we are closer in pleasing the Martian desire before his passing in the fields of Cuba.